Supports from parents, optimism, and life satisfaction in early adolescents - Chong, Shue Ling; Baharudin, Rozumah (Penerbit UTM Press, 2017)
This study examined influences of father and mother support, and optimism on life satisfaction in early adolescents (n = 814; mean age = 13.66 years old) in Malaysia, as well as its variation across gender. Participants were recruited using Probability Proportional to Size (PPS) sampling method from secondary school of four educational zones in Kuala Lumpur. Questionnaires comprising demographic items and measures of the social support, optimism and life satisfaction were self-administered by the students at their respective schools. Data were analyzed using descriptive and inferential statistics including Structural Equation Modeling (SEM) via AMOS. Adolescents who received greater support from their parents reported better life satisfaction. Optimism has an indirect effect on relationship between support from mother and life satisfaction. The model was found as not stable across gender. Support from mother contributed to optimism, and optimism contributed to life satisfaction among adolescent boys, while effect was not found among adolescent girls. Findings imply the importance of considering these variables in prevention and intervention efforts involving early adolescents.